Clustering the countries of the Asia-Pacific by values of inclusive economic growth - S. S. Matveevskii; L. R. Borisova (Вестник университета)
The experience of development banks has led to the conclusion that they directly affect economic growth: projects implementation ensures production of goods and services, creates new workplaces. The growth of gross domestic product is not always inclusive and does not guarantee equal accessibility of all segments of the population to economic opportunities, education, health care, etc. on a constant basis. The Asian Development Bank (hereinafter referred to as the Bank) purposefully influences inclusive economic growth (hereinafter referred to as IEG) in the countries of the Asia-Pacific (hereinafter referred to as APAC) with the help of its own IEG model and allows assessing public administration, economic growth, social support, using 35 indicators, which contributes to reduction of poverty and inequality. For each country the Bank develops its own strategy of cooperation. The authors conducted a hier-archical clustering of the APAC countries based on the values of 24 IEG indicators of the Bank (for two datasets). The APAC countries in each cluster are characterised by approximately the same general level of IEG. The clustering model provides an opportunity to plan projects and assess their influence on IEG, excludes disadvantages of the so-called composite indices that could describe the IEG of a country or region with one value, compensates potential inaccuracies of the basic data.